Deprescription: a global need to rationalize drug prescribing - Vishal, Subhash; Das, Biswadeep; Handu, Shailendra (International Journal of Basic & Clinical Pharmacology, 2020)
Appropriate prescribing and deprescription of unwanted medicines are a global concern. Polypharmacy is common in old age due to multiple comorbidities. This poses many risks that can be prevented by deprescription as a measure of planned reduction in number of medicines no longer needed. For articles to be included in this narrative review, a non-systematic search of deprescription and related term was conducted at PubMed and Google Scholar database. Articles detailing deprescription in general were included whereas those about deprescription in a particular disease or of particular drug groups were excluded. The review discusses about related terms, process of deprescription, when it is to be planned, which patients need deprescription, tools available for appropriate prescription, importance of patient oriented deprescription, actual steps involved in deprescription, present scenario, future scope of trials and formulation of guidelines for deprescription, and finally current state of deprescription in India and actions needed.